The parametric excitation of ion Bernstein modes at the ICR plasma heating in the U-3M torsatron - Olshansky, V.V.; Stepanov, K.N.; Tarasov, I.K.; Tarasov, M.I.; Sitnikov, D.A.; Skibenko, A.I.; Volkov, E.D. (Вопросы атомной науки и техники, 2009)
The results of theoretical and experimental investigations of oscillatory and wave processes at the stellarator plasma
edge are presented. Experimental results were interpreted using the kinetic theory of the electron-ion parametrical
instability. It is shown that the interaction between plasma and the alternating electric field under conditions carried out
in given experiment makes possible a parametric excitation of the ion cyclotron oscillations. Представлені результати теоретичних та експериментальних досліджень осциляторних й хвильових
процесів в периферійній стелараторній плазмі. Експериментальні результати інтерпретуються на основі
кінетичної теорії електрон-іонної параметричної нестійкості. Показано, що дія змінного електричного поля на
плазму в умовах даного експерименту робить можливим параметричне збудження іонних циклотронних
коливань. Представлены результаты теоретических и экспериментальных исследований колебательных и волновых
процессов в периферийной стеллараторной плазме. Экспериментальные результаты интерпретируются на
основе кинетической теории электрон-ионной параметрической неустойчивости. Показано, что воздействие
переменного электрического поля на плазму в условиях данного эксперимента делает возможным
параметрическое возбуждение ионных циклотронных колебаний.